God and sex : what the Bible really says - Coogan, Michael David (New York : Twelve ; London : Little, Brown distributor, 2011)
Biblical scholar Michael Coogan's introductory course on the Old Testament has been a perennial favorite among students at Harvard University. Here, Coogan examines one of the most controversial aspects of the Hebrew Scripture: what the Old Testament really says about sex, and how contemporary understanding of those writings is frequently misunderstood or misrepresented. In the engaging voice generations of students have appreciated, Coogan explores the language and social world of the Bible, showing how much innuendo and euphemism is at play, and illuminating the sexuality of biblical figures as well as God. By doing so, Coogan reveals the immense gap between popular use of Scripture and its original context. Certain to provoke, entertain, and enlighten.--From publisher description.
To know in the biblical sense: speaking of sex -- He will rule over you : the status of women -- As it was in the beginning? : Marriage and divorce -- Thou shalt not : forbidden sexual relationships in the Bible -- Folly in Israel : rape and prostitution -- Fire in the divine loins : God's wives in myth and metaphor.
Includes bibliographical references and index.
Keywords: Sex in the Bible